The Influence of Organizational Culture and Transformational Leadership on Work Productivity Through Employee Job Satisfaction As An Intervening Variable - Fortuna Togatorop, Afrida Deyuwi; Andri, Seno; Mandataris, Mandataris (Cerdika: Jurnal Ilmiah Indonesia, 2024)
This research aims to determine the direct and indirect influence of organizational culture and transformational leadership on work productivity through employee job satisfaction at the Mona Plaza Hotel Pekanbaru. These respondents used a total sampling of 32 respondents. The data collection used was a questionnaire. This research's descriptive quantitative analysis technique uses SMART PLS 4 software. The results of this research show that organizational culture does not affect work productivity, organizational culture has a significant effect on employee job satisfaction, transformational leadership has no effect on work productivity, transformational leadership has a significant effect on employee job satisfaction, employee job satisfaction has a significant effect on work productivity, organizational culture has a significant effect on work productivity through employee job satisfaction, transformational leadership has a significant effect on work productivity through employee job satisfaction.